Testing Marx. Income inequality, concentration, and socialism in late 19th century Germany - Charlotte Bartels; Felix Kersting; Nikolaus Wolf (European Historical Economics Society (EHES), 2021)
We study the dynamics of income inequality, capital concentration, and voting outcomes before 1914. Based on new panel data for Prussian counties and districts we re-evaluate the key economic debate between Marxists and their critics before 1914. We show that the increase in inequality was strongly correlated with a rising capital share, as predicted by Marxists at the time. In contrast, rising capital concentration was not associated with increasing income inequality. Relying on new sectorcounty data, we show that increasing strike activity worked as an offsetting factor. Similarly, the socialists did not directly benefit from rising inequality at the polls, but from the activity of trade unions. Overall, we find evidence for a rise in the bargaining power of workers, which limited the increase in inequality before 1914.
Keywords: D31; D63; J31; N30; 330; Income Inequality; Concentration; Top Incomes; Capital Share; Germany